The role of microglia in glaucoma - trigger and potential target - Chen, Liugui; Yang, Suyu; Wang, Di; Huang, Pingping (Frontiers in Immunology, 2025)
Glaucoma is a neurodegenerative disease characterized by the progressive loss of retinal ganglion cell and optic nerve damage. Recent studies have highlighted the pivotal role of microglia in the onset and progression of glaucoma. This review aims to elucidate the key mechanisms of microglial activation in glaucoma and assess its potential as a therapeutic target for novel treatment strategies. Microglia activation in glaucoma is multifactorial, driven by biomechanical, metabolic, and inflammatory signals. Activated microglia contribute to both neuroinflammatory injury and neuroprotective responses. Their interaction with other kinds of cell establishes a dynamic inflammatory signaling network that exacerbates retinal ganglion cell loss. Furthermore, emerging evidence suggests that key targets in microglial activation, such as APOE, LGALS3, CX3CR1, etc. play critical roles in disease progression, revealing promising targets for therapeutic intervention. Microglia act as central regulators of the retinal immune microenvironment in glaucoma. Their dual role in neurotoxicity and neuroprotection is shaped by complex interactions with other kinds of cell. Targeting microglial activation state and restoring metabolic homeostasis represent promising strategies for the development of pressure-independent treatments for glaucoma.